Cost of capital, fourth edition, workbook and technical supplement - Pratt, Shannon P.; Grabowski, Roger J. (John Wiley & Sons, 2011)
Presents a step-by-step tutorial on estimating certain key components of the cost of equity capital. This title provides a bridge between the theory and some practical applications, such as estimating the cost of capital for real property. It allows the readers to test their comprehension of the concepts and identify areas for a review